Electrolyte of aqueous zinc-iodine battery, aqueous zinc-iodine battery and electrodeless aqueous zinc-iodine battery
By using electrolyte with a quaternary ammonium salt assembler in aqueous zinc-iodine batteries, the problems of iodine positive electrode dissolution and zinc negative electrode dendrites were solved, and the specific capacity, Coulomb efficiency and energy efficiency of the battery were significantly improved.
Patent Information
- Application Number
- CN202411903377.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-02-28
AI Technical Summary
The positive iodine electrode in aqueous zinc-iodine batteries is easily dissolved and polyiodine anions shuttled, while the negative zinc-iodine electrode easily forms dendrites, resulting in attenuation and failure of the battery capacity.
An electrolyte containing a quaternary ammonium salt associative agent is used, the positive electrode electrolyte includes zinc salt, iodized salt, associative agent and water, and the negative electrode electrolyte includes zinc salt and water. Quaternary ammonium salts inhibit the formation of polyiodine anions by forming solid complexes with iodine element, and inhibit the production of zinc dendrites through electrostatic action.
Effectively stabilize the positive and negative electrodes of zinc-iodine batteries, improve the specific capacity, Coulomb efficiency and energy efficiency of the battery, and extend the service life of the battery.
Smart Images

Figure CN119542583A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of aqueous zinc ion batteries, and in particular to an electrolyte of an aqueous zinc iodine battery, an aqueous zinc iodine battery and an electrodeless aqueous zinc iodine battery. Background Art
[0002] To achieve sustainable development, we need to vigorously develop efficient energy storage systems that are compatible with new renewable energy sources. Aqueous zinc-ion batteries have low redox potential (–0.762 V, compared with standard hydrogen electrodes), high theoretical capacity (820 mAh g –1 ), low cost, intrinsic safety and environmental friendliness, it is a promising large-scale energy storage device. Among the various candidate cathodes for zinc-ion batteries, iodine-based cathodes show high specific capacity (211 mAh g –1 ), high redox potential (1.2V) and low toxicity and are favored by researchers.
[0003] In recent years, aqueous zinc-iodine batteries have made great progress. Unfortunately, zinc-iodine batteries still have some defects, which greatly hinder their large-scale application. The iodine positive electrode is easily soluble in iodine-containing electrolytes. – Reaction to form I3 – and I5 – Iodide ions shuttle back and forth on the diaphragm, resulting in loss of active materials and reduced coulombic efficiency, which in turn leads to capacity decay and battery failure. In addition, the zinc metal negative electrode faces serious side reactions. Due to the tip effect, zinc easily accumulates at the tip, and severe dendrite growth easily leads to reduced coulombic efficiency and battery failure. Measures need to be taken to alleviate the above problems, improve the stability of the positive and negative electrode interfaces, and improve the electrochemical performance of aqueous zinc-iodine batteries.
[0004] The above problems can be solved from the aspects of iodine positive electrode design and modification, diaphragm modification, electrolyte engineering and zinc metal negative electrode protection. CN113725414A discloses a positive electrode material for an aqueous zinc-iodine secondary battery, its positive electrode and an aqueous zinc-iodine secondary battery. The positive electrode material includes a binder, a conductive agent and a positive electrode active material, and the positive electrode active material is a composite material of anion exchange fiber / resin and iodine; the positive electrode active material, the conductive agent and the binder are ground and mixed, and N-methylpyrrolidone or distilled water is added after mixing to obtain a positive electrode material slurry; the obtained slurry is coated on the current collector, and the positive electrode is obtained after drying, rolling and cutting. The battery includes a positive electrode, a negative electrode, a diaphragm and an electrolyte, and the diaphragm is located between the positive electrode and the negative electrode, and is stacked in the order of the positive electrode, the diaphragm and the negative electrode into a sandwich-like structure; the electrolyte is a soluble salt of zinc, which is added to the battery when the battery is packaged. The prepared product, the aqueous zinc-iodine battery, shows excellent performance in terms of rate performance and cycle life.
[0005] However, cathode and anode engineering can only solve problems on one side and often involve complex synthesis steps such as atomic layer deposition, limiting their wide applicability. Diaphragm modification requires strict control of its volume and weight to minimize their impact on energy density. In contrast, electrolyte engineering can solve problems in both cathode and anode at the same time and is easy to scale up, with broader application prospects.
[0006] Therefore, it is of great significance to find an aqueous zinc-iodine battery electrolyte that can simultaneously stabilize the positive and negative electrodes of the zinc-iodine battery and improve its electrochemical performance. Summary of the invention
[0007] Aiming at the problem that the iodine positive electrode in an aqueous zinc-iodine battery is easily dissolved and then shuttles on a diaphragm, and the zinc negative electrode is easily dendrite-generated, resulting in battery capacity decay and battery failure, the present invention provides an aqueous zinc-iodine battery electrolyte. The electrolyte can effectively solve the problems of iodine positive electrode dissolution, polyiodide anion shuttle and zinc negative electrode dendrite formation in the aqueous zinc-iodine battery, thereby significantly improving the specific capacity, coulomb efficiency and energy efficiency of the aqueous zinc-iodine battery.
[0008] To achieve the above object, the technical solution adopted by the present invention is:
[0009] An electrolyte for an aqueous zinc-iodine battery, comprising a positive electrode liquid and a negative electrode electrolyte, wherein the positive electrode electrolyte comprises a zinc salt, an iodine salt, an associating agent and water, and the negative electrode electrolyte comprises a zinc salt and water;
[0010] The associative agent is a quaternary ammonium salt, and the general formula is R1R2R3R4NX, wherein R1 to R4 are saturated alkyl carbon chains -C n H 2n+1 , n is a natural number selected from 1 to 4, X is a halogen anion, including F – , Cl – Br – ,I – .
[0011] The invention discloses an aqueous zinc-iodine battery electrolyte. A quaternary ammonium salt associating agent is added for the first time. It is found through experiments that the addition of the quaternary ammonium salt associating agent can stabilize the positive and negative electrodes of the aqueous zinc-iodine battery, effectively solve the problems of iodine positive electrode dissolution, polyiodide anion shuttling, and zinc negative electrode dendrite formation in the zinc-iodine battery, and thus the specific capacity, coulomb efficiency and energy efficiency of the aqueous zinc-iodine battery can be improved at the same time.
[0012] In the present invention, the quaternary ammonium salt associating agent mainly utilizes the strong binding ability between the quaternary ammonium salt associating agent and the iodine element to generate solid R1R2R3R4NI2X, thereby inhibiting the generation of polyiodine anions, thereby effectively solving the problems of iodine positive electrode dissolution and polyiodine anion shuttling. At the same time, the organic quaternary ammonium cation in the quaternary ammonium salt associating agent can be preferentially adsorbed at the tip of zinc dendrite due to electrostatic action, thereby increasing the nucleation overpotential of zinc. Through the electrostatic shielding effect, the generation of zinc dendrites is inhibited. These effects cause the specific capacity, coulomb efficiency and energy efficiency of the battery to be improved.
[0013] The associative agent includes one or more of tetramethylammonium fluoride, tetramethylammonium chloride, tetramethylammonium bromide, tetramethylammonium iodide, ethyltrimethylammonium bromide, ethyltrimethylammonium iodide, methyltriethylammonium fluoride, methyltriethylammonium chloride, methyltriethylammonium bromide, methyltriethylammonium iodide, tetraethylammonium fluoride, tetraethylammonium chloride, tetraethylammonium bromide, tetraethylammonium iodide, trimethylpropylammonium bromide, tripropylmethylammonium fluoride, tripropylmethylammonium iodide, tetrapropylammonium fluoride, tetrapropylammonium chloride, tetrapropylammonium bromide, tetrapropylammonium iodide, tetrabutylammonium fluoride, tetrabutylammonium chloride, tetrabutylammonium bromide, and tetrabutylammonium iodide.
[0014] The iodized salt is selected from one or more of potassium iodide, zinc iodide and sodium iodide.
[0015] There is no special requirement for the type of zinc salt in the present invention, and the zinc salt can be selected from conventional types in the art, such as one or more of zinc sulfate, zinc iodide, zinc trifluoromethanesulfonate, zinc bistrifluoromethanesulfonyl imide, zinc tetrafluoroborate, zinc hexafluorophosphate, zinc chloride, zinc acetate and zinc nitrate;
[0016] The molar concentration of the associating agent in the positive electrode electrolyte is 0.1 to 2.0 mol L –1 ; The molar concentration of zinc salt is 0.1~5.0mol L –1 ; The molar concentration of iodized salt is 0.1~3.0mol L –1 The molar concentration of zinc salt in the negative electrode electrolyte is 0.1 to 5.0 mol L –1 .
[0017] The molar concentration of the associating agent in the positive electrode electrolyte is 0.1 to 1.0 mol L –1 ; The molar concentration of iodized salt is 0.1-0.5 mol L –1 The molar concentration of zinc salt in the negative electrode electrolyte is 0.1 to 2.0 mol L –1 .
[0018] The molar ratio of the associating agent in the positive electrode electrolyte to the iodide ions in the iodide salt is 2:0.5-1, and more preferably the molar ratio of the associating agent to the iodide ions in the iodide salt is 2:1.
[0019] The present invention also provides an aqueous zinc-iodine battery, comprising a positive electrode current collector, a diaphragm, a zinc negative electrode and an electrolyte, wherein the positive electrode electrolyte in the electrolyte is selected from the positive electrode electrolyte as described above, and the negative electrode electrolyte consists of a zinc salt and water.
[0020] The aqueous zinc-iodine battery assembled based on the above-mentioned electrolyte avoids the decrease in battery efficiency caused by the shuttling of iodine ions at the positive electrode and the associating agent to form polyiodine anions. The associating agent can also inhibit zinc dendrites. The battery has the excellent performance of high specific capacity, high coulombic efficiency and high energy efficiency.
[0021] In the aqueous zinc-iodine battery, the positive electrode current collector is selected from one or more of carbon paper, carbon cloth, carbon mesh, activated carbon-coated carbon paper, activated carbon-coated carbon cloth, and activated carbon-coated carbon mesh; the separator is selected from one or more of glass fiber membrane, Nafion membrane, PP membrane, and PE membrane;
[0022] The zinc negative electrode is selected from one or more of zinc foil, zinc powder and zinc alloy foil.
[0023] The present invention also provides an electrodeless aqueous zinc-iodine battery, comprising a positive electrode current collector, a separator, a negative electrode current collector and an electrolyte, wherein the positive electrode electrolyte in the electrolyte is selected from the positive electrode electrolyte, and the negative electrode electrolyte is composed of zinc salt and water. The electrodeless aqueous zinc-iodine battery assembled using the electrolyte disclosed in the present invention can be stably circulated and has a high coulombic efficiency.
[0024] In the electrodeless aqueous zinc-iodine battery, the positive electrode current collector is selected from one or more of carbon paper, carbon cloth, carbon mesh, activated carbon-coated carbon paper, activated carbon-coated carbon cloth, and activated carbon-coated carbon mesh;
[0025] The diaphragm is selected from one or more of a glass fiber membrane, a Nafion membrane, a PP membrane and a PE membrane;
[0026] The negative electrode current collector is selected from one or more of copper foil, copper mesh, titanium foil, titanium mesh, stainless steel foil and stainless steel mesh.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] (1) The quaternary ammonium salt associating agent in the present invention mainly utilizes its strong binding ability with iodine element to generate solid R1R2R3R4NI2X, inhibiting the generation of polyiodide anions, thereby effectively solving the problem of iodine positive electrode dissolution and polyiodide anion shuttling.
[0029] (2) The organic quaternary ammonium cations in the aqueous zinc-iodine battery electrolyte disclosed in the present invention can be preferentially adsorbed at the tip of zinc dendrites due to electrostatic action, thereby inhibiting the generation of zinc dendrites through electrostatic shielding.
[0030] (3) The aqueous zinc-iodine battery electrolyte disclosed in the present invention can increase the nucleation overpotential of zinc, achieve uniform deposition of zinc, and inhibit the generation of zinc dendrites.
[0031] (4) When the aqueous zinc-iodine battery electrolyte disclosed in the present invention is applied to zinc-iodine batteries, the problems of iodine positive electrode dissolution, polyiodine anion shuttling, and zinc negative electrode dendrite formation in zinc-iodine batteries can be effectively solved, thereby significantly improving the specific capacity, coulomb efficiency, and energy efficiency of aqueous zinc-iodine batteries, and having good application prospects.
[0032] (5) When the aqueous zinc-iodine battery electrolyte disclosed in the present invention is applied to an electrodeless aqueous zinc-iodine battery, it can circulate stably and has a high coulombic efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 The binding energy of the quaternary ammonium salt associating agent and I2 calculated in the electrolyte prepared in Examples 1 to 4.
[0034] Figure 2 This is a scanning electron microscope photograph of the positive electrode of a zinc-iodine full battery assembled with the electrolyte prepared in Comparative Example 1 and Examples 1 to 4 and charged to 1.6V.
[0035] Figure 3 This is the X-ray photoelectron spectrum of the positive electrode of the zinc-iodine full battery assembled with the electrolyte prepared in Comparative Example 1 and charged to 1.6V.
[0036] Figure 4 This is the X-ray photoelectron spectrum of the positive electrode of a zinc-iodine full battery assembled with the electrolyte prepared in Example 1 and charged to 1.6V.
[0037] Figure 5 This is the X-ray photoelectron spectrum of the positive electrode of a zinc-iodine full battery assembled with the electrolyte prepared in Example 2 and charged to 1.6V.
[0038] Figure 6 This is the X-ray photoelectron spectrum of the positive electrode of a zinc-iodine full battery assembled with the electrolyte prepared in Example 3 and charged to 1.6V.
[0039] Figure 7 This is the Fourier infrared spectrum of the cathode products of implementations 1 to 3.
[0040] Figure 8 This is a scanning electron microscope photograph of the zinc foil after the first round of zinc deposition in the Zn||Zn symmetric battery assembled with the electrolyte prepared in Comparative Example 1.
[0041] Fig. 9 This is a scanning electron microscope photograph of the zinc foil after the first round of zinc deposition in the Zn||Zn symmetric battery assembled with the electrolyte prepared in Example 1.
[0042] Fig.10 This is a scanning electron microscope photograph of the zinc foil after the first round of zinc deposition in the Zn||Zn symmetric battery assembled with the electrolyte prepared in Example 2.
[0043] Fig.11 This is a scanning electron microscope photograph of the zinc foil after the first round of zinc deposition in the Zn||Zn symmetric battery assembled with the electrolyte prepared in Example 3.
[0044] Fig.12 This is a scanning electron microscope photograph of the zinc foil after the first round of zinc deposition in the Zn||Zn symmetric battery assembled with the electrolyte prepared in Example 4.
[0045] Fig.13 It is a schematic diagram of the initial state, charging state and discharging state of the electrodeless zinc-iodine battery of the present invention. DETAILED DESCRIPTION
[0046] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with embodiment. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. Those skilled in the art can make modifications or equivalent substitutions based on the understanding of the technical scheme of the present invention without departing from the spirit and scope of the technical scheme of the present invention, and all should be included in the protection scope of the present invention.
[0047] The raw materials used in the following specific embodiments are all purchased from the market.
[0048] Example 1
[0049] Electrolyte preparation: zinc sulfate is selected as zinc salt, potassium iodide is selected as iodine salt, water is used as solvent, and tetramethylammonium fluoride is selected as quaternary ammonium salt associating agent. Zinc sulfate and water are mixed to obtain the negative electrode electrolyte. The concentration of zinc sulfate is 2 mol L –1 Potassium iodide, tetramethylammonium fluoride and water are mixed to obtain the positive electrode electrolyte. The concentration of potassium iodide is 0.4 mol L –1 The concentration of tetramethylammonium fluoride is 0.2 mol L –1 .
[0050] Comparative Example 1
[0051] Electrolyte preparation: zinc sulfate is selected as zinc salt, potassium iodide is selected as iodine salt, and water is used as solvent. Zinc sulfate and water are mixed to obtain the negative electrode electrolyte. The concentration of zinc sulfate is 2 mol L –1 Potassium iodide is mixed with water to obtain the positive electrode electrolyte. The concentration of potassium iodide is 0.4 mol L –1 .
[0052] Example 2
[0053] The preparation of the electrolyte is substantially the same as that in Example 1, except that the quaternary ammonium salt associating agent tetramethylammonium fluoride is replaced by tetramethylammonium chloride.
[0054] Example 3
[0055] The preparation of the electrolyte is substantially the same as that in Example 1, except that the quaternary ammonium salt associating agent tetramethylammonium fluoride is replaced by tetramethylammonium bromide.
[0056] Example 4
[0057] The preparation of the electrolyte is substantially the same as that in Example 1, except that the quaternary ammonium salt associating agent tetramethylammonium fluoride is replaced by tetramethylammonium iodide.
[0058] Example 5
[0059] The preparation of the electrolyte is basically the same as that in Example 1, except that the concentration of the quaternary ammonium salt associating agent tetramethylammonium fluoride is replaced by 0.1 mol L –1 .
[0060] Example 6
[0061] The preparation of the electrolyte is basically the same as that in Example 1, except that the concentration of tetramethylammonium fluoride as the quaternary ammonium salt associating agent is replaced by 0.25 mol L –1 .
[0062] Application Example 1: Assembling a zinc-iodine full battery
[0063] Using zinc foil as the negative electrode, activated carbon-coated carbon paper as the positive electrode current collector, glass fiber as the separator, and the solutions prepared in Examples 1 to 6 and Comparative Example 1 as the electrolyte, a zinc-iodine full battery was assembled for testing.
[0064] The full cells assembled using the electrolytes of Examples 1 to 6 and Comparative Example 1 were tested at 0.2 A g –1 The charge and discharge tests were carried out in the voltage range of 0.6-1.6V at a current density of . The average coulombic efficiency and average energy efficiency of the battery in the first 100 cycles are listed in Table 1 below.
[0065] Table 1 Performance of zinc-iodine full batteries assembled with electrolytes of the embodiments and comparative examples
[0066]
[0067]
[0068] From the data in Table 1, it can be seen that, compared with Comparative Example 1, Examples 1 to 6 have higher average coulombic efficiency and energy efficiency at the same charge and discharge current density. In addition, these two indicators are Example 1> Example 2> Example 3> Example 4. Figure 1The calculated binding energies of the quaternary ammonium salt associating agent and I2 in the electrolytes prepared in Examples 1 to 4. The results show that the binding energies of Examples 1 to 4 are -9.91 eV, -5.54 eV, -5.43 eV, and -5.31 eV, respectively, indicating that the associating ability for I2 is Example 1> Example 2> Example 3> Example 4, which is the same as the trend of the coulomb efficiency and energy efficiency in Table 1. This shows that among the four quaternary ammonium salts, tetramethylammonium fluoride has the best effect, and is far superior to the case where no quaternary ammonium salt is added in Comparative Example 1.
[0069] The average coulombic efficiency and energy efficiency of Examples 1, 5, and 6 in Table 1 all show a trend of Example 1 > Example 5 and Example 1 > Example 6, indicating that the concentration of tetramethylammonium fluoride associative agent is 0.2 mol L –1 When the coulombic efficiency and energy efficiency of the zinc-iodine full battery are maximized.
[0070] The full cells assembled using the electrolytes of Examples 1 to 4 and Comparative Example 1 were tested at 0.05 A g –1 The charge and discharge tests were carried out in the voltage range of 0.6 to 1.6 V at a current density of , and the first coulombic efficiency and specific capacity of the battery are listed in Table 2 below.
[0071] Table 2 Full battery charge and discharge test performance of electrolytes assembled in the embodiments and comparative examples
[0072] serial number First coulombic efficiency (%) <![CDATA[Specific capacity (mAh g –1 )]]> Comparative Example 1 71.45 99.9 Example 1 87.66 156.4 Example 2 87.25 135.5 Example 3 87.22 115.4 Example 4 87.20 113.6
[0073] Comparing the data in Table 2, it can be seen that, compared with Comparative Example 1, Examples 1 to 4 have higher first coulombic efficiency and specific capacity at the same charge and discharge current density. In addition, these two indicators are Example 1> Example 2> Example 3> Example 4.
[0074] The zinc-iodine full batteries assembled using the electrolytes of Comparative Example 1 and Examples 1 to 4 were tested at 0.05 Ag. –1 The positive electrode was charged to 1.6 V at a current density of 1.5 V and the positive electrode morphology was observed using a scanning electron microscope. Figure 2 As shown. In both Comparative Example 1 and Examples 1 to 4, small flakes were formed on the positive electrode surface. In Comparative Example 1, these flakes were irregularly distributed on the electrode surface. In contrast, in Examples 1 to 4, the flakes were more uniformly and tightly attached to the surface of the block activated carbon particles, indicating that the product generated after adding the associating agent has a stronger affinity for the activated carbon current collector.
[0075] The zinc-iodine full batteries assembled using the electrolytes of Comparative Example 1 and Examples 1 to 3 were tested at 0.05 Ag. –1 The positive electrode charged to 1.6 V at a current density of 1.5 was characterized by X-ray photoelectron spectroscopy, such as Figures 3 to 6As shown. For the electrode prepared in the electrolyte in Comparative Example 1, Figure 3 The I 3d X-ray photoelectron spectrum shows two distinct peak pairs corresponding to I3 – and I5 – Species. Figure 4 In the electrolyte of Example 1, the I 3d X-ray photoelectron spectrum showed two peaks, confirming the presence of I–F on the electrode, and the F 1s X-ray photoelectron spectrum also showed I–F and F – These findings together confirm the existence of I–F on the electrode surface. Figure 5 and Figure 6 In the electrolytes of Examples 2 and 3, the I 3d X-ray photoelectron spectrum shows the peaks of I–Cl and I–Br, and the peaks in the Cl 2p X-ray photoelectron spectrum and the peaks in the Br X-ray photoelectron spectrum further confirm the existence of I–Cl and I–Br, respectively. This indicates that the iodide ions in the electrolyte associate with the associating agent, blocking the shuttling of the polyiodide anions.
[0076] Fourier transform infrared spectroscopy was performed on the positive electrode products of Examples 1 to 3 respectively. Figure 7 In the Fourier transform infrared spectrum, 939, 1126, 1464, 2852 and 2922 cm –1 The peaks at 2 and 3 correspond to the symmetric stretching vibrations of C–N (ν s (C–N)), the rocking vibration of CH3 (r(CH3)), the deformation vibration of CH3 (δ(CH3)), the symmetric stretching vibration of C–N (ν s (C–N)), the rocking vibration of CH3 (r(CH3)), the deformation vibration of CH3 (δ(CH3)), the symmetric stretching vibration of CH3 (ν s (CH3)) and the asymmetric stretching vibration of CH3 (ν as (CH3)), confirming the presence of (CH3)4N– in the solid powder. Figures 3 to 6 From the results of X-ray photoelectron spectroscopy, it can be proved that the compositions of the positive electrode products of the electrolytes of Examples 1 to 3 when charged to 1.6V are (CH3)4NI2F, (CH3)4NI2Cl and (CH3)4NI2Br respectively.
[0077] Application Example 2: Assembling Zn||Zn symmetrical battery
[0078] Using zinc foil as electrode and glass fiber as separator, the solutions prepared in Examples 1 to 4 and Comparative Example 1 were used as electrolytes to assemble Zn||Zn symmetrical batteries for testing. The current density and capacity of the charge and discharge cycles were 4 mA cm –2 and 1mAh cm –2The nucleation overpotential and cycle time of the cells are listed in Table 3 below.
[0079] Table 3 Charge and discharge performance of Zn||Zn symmetric batteries assembled with electrolytes of the embodiments and comparative examples
[0080] serial number Nucleation overpotential (mV) Cycle time (h) Comparative Example 1 99.5 22 Example 1 127.0 >1400 Example 2 112.1 >1400 Example 3 111.5 >1400 Example 4 109.6 >1400
[0081] Comparing the data in Table 3 with the data in Table 2, it can be seen that, compared with Comparative Example 1, Examples 1 to 4 have higher nucleation overpotentials and cycle times at the same current density. In addition, the nucleation overpotential of Example 1>Example 2>Example 3>Example 4.
[0082] Figure 8 Scanning electron microscope photographs of the zinc foil at different magnifications after the first round of zinc deposition in the Zn||Zn symmetric battery assembled with the electrolyte prepared in Comparative Example 1 show that the foil has a loose morphology and has dendrites.
[0083] Figures 9 to 12 The following are scanning electron microscope photographs at different magnifications of the zinc foil after the first zinc deposition in the symmetrical batteries assembled with the electrolytes prepared in Examples 1 to 4, respectively. Figures 9 to 12 A uniform and dense deposition layer was formed in the samples without dendrite formation. Figures 9 to 12 It can be found that when tetramethylammonium fluoride is used as the associating agent, the zinc deposition morphology is the most uniform and flat, and then as the associating agent used changes from tetramethylammonium chloride to tetramethylammonium bromide and then to tetramethylammonium iodide, the zinc deposition gradually becomes uneven. This is consistent with the trend of the binding ability of these four associating agents with I2.
[0084] Application Example 3: Assembly of Electrodeless Zinc-Iodine Battery
[0085] An electrodeless zinc-iodine battery was assembled using copper foil as the negative electrode current collector, glass fiber as the separator, activated carbon-coated carbon paper as the positive electrode current collector, and the solution prepared in Example 4 as the electrolyte. The assembled electrodeless zinc-iodine battery was heated to 1Ag. –1 The charge and discharge tests were carried out at a current density of 0.6 to 1.6 V. The composition of the initial state, charging state and discharge state of the electrodeless zinc-iodine battery is as follows: Fig.13 As shown in the figure, during the charging process, a layer of R1R2R3R4NI2X will be deposited on the surface of the positive electrode current collector as the positive active material of the association, and zinc metal will be deposited on the surface of the negative electrode current collector. During the discharge process, the two electrodes will be converted into I – and Zn 2+ The coulombic efficiency of the assembled electrodeless zinc-iodine battery is listed in Table 4 below.
[0086] Table 4 Coulombic efficiency of the electrodeless zinc-iodine battery assembled with the electrolyte of Example 4
[0087] Number of cycles Coulomb efficiency (%) 1 62.19 2 80.67 3 84.20 4 86.13 5 88.02 6 88.93 7 89.94
[0088] From the data in Table 4, it can be seen that the aqueous zinc-iodine battery electrolyte disclosed in the present invention can realize the construction of an electrodeless aqueous zinc-iodine battery with stable circulation and high coulombic efficiency.
[0089] In summary, when the aqueous zinc-iodine battery electrolyte disclosed in the present invention is applied to zinc-iodine batteries, it can effectively solve the problems of iodine positive electrode dissolution, polyiodine anion shuttle, and zinc negative electrode dendrite formation in zinc-iodine batteries, thereby significantly improving the specific capacity, coulomb efficiency, and energy efficiency of aqueous zinc-iodine batteries. At the same time, the aqueous zinc-iodine battery electrolyte disclosed in the present invention can realize the construction of high coulomb efficiency electrodeless aqueous zinc-iodine batteries.
Claims
1. An electrolyte for an aqueous zinc-iodine battery, characterized in that: It comprises a positive electrode liquid and a negative electrode electrolyte, wherein the positive electrode electrolyte comprises an iodine salt, an associating agent and water, and the negative electrode electrolyte comprises a zinc salt and water; The associative agent is a quaternary ammonium salt, and the general formula is R1R2R3R4NX, wherein R1 to R4 are saturated alkyl carbon chains -C n H 2n+1 , n is a natural number selected from 1 to 4, X is a halogen anion, including F – , Cl – Br – ,I – .
2. The electrolyte of the aqueous zinc-iodine battery according to claim 1, characterized in that: The associative agent includes one or more of tetramethylammonium fluoride, tetramethylammonium chloride, tetramethylammonium bromide, tetramethylammonium iodide, ethyltrimethylammonium bromide, ethyltrimethylammonium iodide, methyltriethylammonium fluoride, methyltriethylammonium chloride, methyltriethylammonium bromide, methyltriethylammonium iodide, tetraethylammonium fluoride, tetraethylammonium chloride, tetraethylammonium bromide, tetraethylammonium iodide, trimethylpropylammonium bromide, tripropylmethylammonium fluoride, tripropylmethylammonium iodide, tetrapropylammonium fluoride, tetrapropylammonium chloride, tetrapropylammonium bromide, tetrapropylammonium iodide, tetrabutylammonium fluoride, tetrabutylammonium chloride, tetrabutylammonium bromide, and tetrabutylammonium iodide; The iodized salt is selected from one or more of potassium iodide, zinc iodide and sodium iodide.
3. The electrolyte of the aqueous zinc-iodine battery according to claim 1, characterized in that: The zinc salt is selected from one or more of zinc sulfate, zinc iodide, zinc trifluoromethanesulfonate, zinc bistrifluoromethanesulfonyl imide, zinc tetrafluoroborate, zinc hexafluorophosphate, zinc chloride, zinc acetate and zinc nitrate.
4. The electrolyte of the aqueous zinc-iodine battery according to claim 1, characterized in that: The molar concentration of the associating agent in the positive electrode electrolyte is 0.1 to 2.0 mol L –1 ; The molar concentration of zinc salt is 0.1~5.0mol L –1 ; The molar concentration of iodized salt is 0.1~3.0mol L –1 The molar concentration of zinc salt in the negative electrode electrolyte is 0.1 to 5.0 mol L –1 .
5. The electrolyte of the aqueous zinc-iodine battery according to claim 1, characterized in that: The molar concentration of the associating agent in the positive electrode electrolyte is 0.1 to 1.0 mol L –1 ; The molar concentration of iodized salt is 0.1-0.5 mol L –1 The molar concentration of zinc salt in the negative electrode electrolyte is 0.1 to 2.0 mol L –1 .
6. The electrolyte of the aqueous zinc-iodine battery according to claim 1, characterized in that: The molar ratio of the associating agent in the positive electrode electrolyte to the iodide ions in the iodine salt is 2:0.5-1.
7. An aqueous zinc-iodine battery, comprising a positive electrode current collector, a separator, a zinc negative electrode and an electrolyte, characterized in that: The positive electrode electrolyte in the electrolyte is selected from the positive electrode electrolyte as described in any one of claims 1 to 6, and the negative electrode electrolyte consists of zinc salt and water.
8. The aqueous zinc-iodine battery according to claim 7, characterized in that: The positive electrode current collector is selected from one or more of carbon paper, carbon cloth, carbon mesh, activated carbon-coated carbon paper, activated carbon-coated carbon cloth, and activated carbon-coated carbon mesh; The diaphragm is selected from one or more of a glass fiber membrane, a Nafion membrane, a PP membrane and a PE membrane; The zinc negative electrode is selected from one or more of zinc foil, zinc powder and zinc alloy foil.
9. An electrodeless aqueous zinc-iodine battery, comprising a positive electrode current collector, a separator, a negative electrode current collector and an electrolyte, characterized in that: The positive electrode electrolyte in the electrolyte is selected from the positive electrode electrolyte as described in any one of claims 1 to 6, and the negative electrode electrolyte consists of zinc salt and water.
10. The electrodeless aqueous zinc-iodine battery according to claim 9, characterized in that: The positive electrode current collector is selected from one or more of carbon paper, carbon cloth, carbon mesh, activated carbon-coated carbon paper, activated carbon-coated carbon cloth, and activated carbon-coated carbon mesh; The diaphragm is selected from one or more of a glass fiber membrane, a Nafion membrane, a PP membrane and a PE membrane; The negative electrode current collector is selected from one or more of copper foil, copper mesh, titanium foil, titanium mesh, stainless steel foil and stainless steel mesh.
Citation Information
Patent Citations
Battery and preparation method of iodine electrode material and electrolyte
CN117039207A
Electrolyte for aqueous zinc-bromine battery containing bromine complexing agent and metal ion additive, and aqueous zinc-bromine non-flow battery containing same
US20240021887A1
Four-electron conversion reaction-based aqueous zinc-iodine battery and electrolyte thereof
WO2021228001A1